PENGGUNAAN PROFILE, STATISTIC, DAN STRATIFY D ALAM MENGAUDIT ACCOUNT RECEIVABLE (STUDI KASUS) - Ali Masjono; Agus Purwaji (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
Computer Assisted Audit Techniques (CAATs) refers to the software ACL (Audit Command Language Version 9), is useful to calculate profile, statistics, and stratibi automatically. It uses to know the whether the occurrence of anomalies in an Account Receivable (AR) balances information. The field amount were used where the final balances ofAR are stored. This research has discussed the 161 records from 772 records have negative balances or 27.72% of total AR Balances. The research has examined the company policy against negative balances. Does a negative balance can be converted into goods or collateral accounts. If a positive balance equal to a negative balance, the AR balance will be zero. This leads to miss interpretation of the AR and affect the credibility of sales information, which the Information is as no sale occurred when credit sales did occurred.